“Secret-Service buffoon to the Woman’s Cause”: Mina Loy’s ambivalent commitments - Margaret GILLESPIE (E-REA)
This article explores issues of commitment in relation to the early writings of woman modernist Mina Loy (1882-1966). It will be argued that it is not simply by way of her diverse aesthetic output, but also through the very instability of her poetic voice, that Loy troubles established narratives of modernist commitment, and complicates contemporary first-wave feminist debates, at once affirming and challenging the theories of her peers, and placing, in her own singular fashion, the “woman’s cause” at the heart of her artistic practice.